Supramolecular Systems for Gene and Drug Delivery - Ostos, Francisco José; Lebrón, José Antonio; López-Cornejo, Pilar (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Dear Colleagues,Supramolecular systems (calixarenes, cyclodextrins, polymers, peptides, etc.) have attracted special attention due to their excellent therapeutic properties for biomedical applications such as gene and drug delivery. Numerous biomaterials-based supramolecular systems have been developed in the last decade for enhancing of biocompatibility and pharmacological activity. In particular, supramolecular nanomaterials are considered a hot research topic, because nanomedicine has become an interesting tool for the treatment of genetic diseases or cancer. Nevertheless, novel systems and their properties are being continuously studied, contributing to the development of efficient delivery systems.This Special Issue provides and highlights current progress in the use of the supramolecular systems for boosting gene and drug delivery. Preparation, characterization, and use of these systems, as well as the latest developments in this research field, are especially welcome.Authors are encorauged to submit original research articles and reviews in this promising research field.